2014
DOI: 10.1039/c4nr01016g
|View full text |Cite
|
Sign up to set email alerts
|

A flux induced crystal phase transition in the vapor–liquid–solid growth of indium-tin oxide nanowires

Abstract: Single crystalline metal oxide nanowires formed via a vapor-liquid-solid (VLS) route provide a platform not only for studying fundamental nanoscale properties but also for exploring novel device applications. Although the crystal phase variation of metal oxides, which exhibits a variety of physical properties, is an interesting feature compared with conventional semiconductors, it has been difficult to control the crystal phase of metal oxides during the VLS nanowire growth. Here we show that a material flux c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…1a which is attributed to the limited miscibility and different ionic radii of Sn and In. We do not observe the fluorite structure of In x Sn y O 3.5 as shown recently by Meng et al [19] who observed a flux-induced crystal phase transition in the VLS growth of Sn-doped In 2 O 3 NWs. The PL of the Sn-doped In 2 O 3 NWs was found to be broad with a maximum at λ = 500 nm or 2.5 eV that shifts to 450 nm or ≈2.8 eV upon reducing the content of Sn to 1 % which also results into an increase in the carrier lifetime as shown previously by time-resolved PL [11].…”
Section: Resultssupporting
confidence: 53%
“…1a which is attributed to the limited miscibility and different ionic radii of Sn and In. We do not observe the fluorite structure of In x Sn y O 3.5 as shown recently by Meng et al [19] who observed a flux-induced crystal phase transition in the VLS growth of Sn-doped In 2 O 3 NWs. The PL of the Sn-doped In 2 O 3 NWs was found to be broad with a maximum at λ = 500 nm or 2.5 eV that shifts to 450 nm or ≈2.8 eV upon reducing the content of Sn to 1 % which also results into an increase in the carrier lifetime as shown previously by time-resolved PL [11].…”
Section: Resultssupporting
confidence: 53%
“…Au film was preheated at the growth temperature 800 °C for 20 minutes then the ArF excimer laser was ablated to SnO 2 target material for the nanowire growth. After 30 minute, the sample was cool down to room temperature for 30 minutes36373839; these were done more than six times. The Cr layer was lifted off by Cr etchant solution.…”
Section: Methodsmentioning
confidence: 99%
“…This technique is widely used, highly efficient, and accepted for producing 1D nanomaterials, where the produced nanowires are grown on the metal-coated surface. 49,[77][78][79] Budak et al 80 mentioned that one-dimensional crystalline SnO 2 nanowires had been produced by the carbothermal reduction of tin oxide nanopowder followed by thermal evaporation of the reduced vapor precursor and growth via the vaporliquid-solid (VLS) growth mechanism. Similarly, Choi 81 synthesized metal oxide nanowires for optoelectronics using a vapor-liquid-solid (VLS) growth mechanism.…”
Section: Synthesis Of Tin Oxide and Tin-oxide-based Nanocompositesmentioning
confidence: 99%